1997
DOI: 10.1002/(sici)1096-9888(199701)32:1<71::aid-jms452>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Group Migration in the Fragmentation of Bistrimethylsilyl Ethers of Diols Separated by Rigid Groups

Abstract: Two fragmentations of (CH3)3SiO-CR2-X-CR2-OSi(CH3)3, where X is a rigid group such as a triple bond or an aromatic ring, are losses of a methyl or R group (where R is H or alkyl). The metastable-ion dissociations of [M-R]+ and [M-CH3]+ ions include the rearrangement of a trimethylsilyl (TMS) cation and a (CH3)2Si = O neutral species through an ion-neutral complex. On the basis of tandem mass spectrometry (MS/MS), exact mass measurement and isotopic labeling experiments, it has been established that the two tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These ions are formed even for compounds with greatly separated TMS groups as, for example, 3,17-di-TMS ethers of steroidal phosphate derivatives. 77 For several trimethylsilylated derivatives of rather rigid benzenedimethanols and acetylenic diols, it was shown 78 that these ions are formed from the [M -CH 3 ] + ions due to a migration of the neutral species (CH 3 ) 2 Si = O most likely through an ion-neutral complex. Further decomposition of the m/z 147 ions proceeds via the loss of CH 2 O (to m/z 117) or CH 4 (to m/z 131).…”
mentioning
confidence: 99%
“…These ions are formed even for compounds with greatly separated TMS groups as, for example, 3,17-di-TMS ethers of steroidal phosphate derivatives. 77 For several trimethylsilylated derivatives of rather rigid benzenedimethanols and acetylenic diols, it was shown 78 that these ions are formed from the [M -CH 3 ] + ions due to a migration of the neutral species (CH 3 ) 2 Si = O most likely through an ion-neutral complex. Further decomposition of the m/z 147 ions proceeds via the loss of CH 2 O (to m/z 117) or CH 4 (to m/z 131).…”
mentioning
confidence: 99%
“…8 On the one hand, the experimental study shows that both metastable ions fragment to give the m/z 131 ion (1) by the loss of an ethyl radical and by the loss of a methane molecule, respectively. On the other hand, calculations indicate that the more stable structure of m/z 131 thus formed is not the open structure 1a as previously presumed, 6,7 but the cyclic structure 1b (Scheme 1). In order to generate new silicon-containing ions by using common reagents such as hexamethyldisiloxane or hexamethyldisilane, the ion-molecule reactions of the m/z 147 and m/z 131 ions with neutral molecules, such as water, 7 ammonia and carbonyl compounds 9 are currently under study in this laboratory.…”
Section: Introductionmentioning
confidence: 63%
“…4 Trimethylsilylated ions undergo rearrangements involving the intermediacy of ion-neutral complexes, as shown by Longevialle 5 in the case of the trimethylsilyl derivatives of hydroxysteroids. For instance, Gross and coworkers 6 have shown that ionized bis(trimethylsilyl) ethers of diols yield the (CH 3 ) 3 SiOSi(CH 3 ) 2 + (m/z 147) ion. This ion is identical to that formed by loss of a methyl group from ionized hexamethyldisiloxane (CH 3 ) 3 SiOSi(CH 3 ) 3 (m/z 162).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that ion-dipole complexes can have an important mechanistic participation in this type of systems has been previously advanced to account for the trimethylsilyl group migration observed in mass spectral fragmentations of trimethylsilyl ethers 33 , and for the outcome of ion-molecule reactions between silyl cations and ketones 34 . This ease of migration by methylsilyl cations is supported by preliminary ab initio calculations on model silyl systems that show such rearrangements to occur without any formal activation energy 35 .…”
Section: Resultsmentioning
confidence: 99%